A Finite Difference Scheme for the Modeling of a Direct Methanol Fuel Cell - Nguyen, Hoc-Tran; Nguyen, Tuan-Anh; Ho, Van Thi Thanh (International Journal of Advanced Engineering Research and Science, 2022)
A one dimensional (1-D), isothermal model for a direct methanol fuel cell (DMFC) is introduced and solved numerically by a simple finite difference scheme. By using numerical calculation, the model model can be extended to more complicated situation which can not be solved analytically. The model considers the kinetics of the multi-step methanol oxidation reaction at the anode. Diffusion and crossover of methanol are taken into account and the reduced potential of the cell due to the crossover is then estimated. The calculated results are compared to the experimental data from literature. This finite difference scheme can be rapidly solved with high accuracy and it is suitable for the extension of the model to more detail or to higher dimension.